Enhancing Cultural Identity Through Academic Collaboration at the Workshop for Documenting the Traditional Architecture of the Tuha Pucok Krueng Mosque in Pidie Jaya - Sabilla, Arissa; Lisa, Nova Purnama; Rikza, Rikza; Siregar, Putri Fikadilah; Sinurat, Dian Aswatul; Yosantia, Muhammad Ferah; Juanda, Ari; Muammar, Rajib (Universitas Muhammadiyah Aceh, 2025)
The purpose of this community service activity is to strengthen cultural identity through a construction documentation workshop, addressing the fading cultural identity. The methods used in this community service activity include outreach, workshops, and training. The activity was implemented as part of the SIMPORA XVI 2025 Expo, involving lecturers, students, business actors, and cultural communities. The activities included outreach, design workshops, exhibitions, and interactive dialogue between academics and the community. The results of this activity indicate that academic collaboration can enhance students' understanding of the importance of cultural preservation, encourage active community participation in showcasing works based on local wisdom, and produce building designs that incorporate cultural values through the documentation of the traditional construction of the Tuha Pucok Krueng Mosque. This activity concludes that strengthening cultural identity can be achieved if universities consistently act as community partners in building collective awareness and making a tangible contribution to the sustainability of local culture.